Feasibility of a trauma-informed parent–teacher cooperative training program for Syrian refugee children with autism. (July 2019) - Dababnah, Sarah; Habayeb, Serene; Bear, Benjamin J; Hussein, Dana
Although the number of Syrians affected by the civil war rises, little work has been done to address the needs of Syrian refugee children with autism spectrum disorder. This research aimed to test the feasibility and acceptability of a culturally sensitive intervention developed specifically for children with autism spectrum disorder affected by trauma. Local partners advised the program team on cultural norms. Nine parents and 11 teachers were recruited to participate in 12-week parent–teacher cooperatives in a large Turkish city. We used qualitative methods to analyze interviews with each participant after intervention completion. A total of 14 participants completed the program (70%). All interviewees were women and Syrian refugees. Local political events, transportation costs and safety, and illnesses impacted attrition and attendance. All participants were satisfied with program content, including gains in autism knowledge, behavior management skills, and social support. Program-related challenges included applying skills to nonverbal children. The majority of participants made recommendations for program improvement, including a need for services outside urban areas. Flexible program delivery methods, including online options, might better accommodate participants unable to travel due to distance, political unrest, or safety. More research is needed to rigorously test program outcomes and to evaluate efforts to train local program leaders.